Mutant Influenza Viruses with a Defective NS1 Protein Cannot Block the Activation of PKR in Infected Cells - Hatada, Eriko (American Society for Microbiology, 1999)
A short model genome RNA and also the genome RNA of influenza A virus bearing both 5′- and 3′-terminal common sequences activated the interferon-induced double-stranded-RNA-dependent protein kinase, PKR, by stimulating autophosphorylation in vitro. The activated PKR catalyzed phosphorylation of the alpha subunit of eucaryotic translation initiation factor 2 (eIF2α). The NS1 protein efficiently eliminated the PKR-activating activity of these RNAs by binding to them. Two mutant NS1 proteins, each harboring a single amino acid substitution at different regions, exhibited temperature sensitivity in their RNA binding activity in the mutant virus-infected cell lysates as well as when they were prepared as fusion proteins expressed in bacteria. The virus strains carrying these mutant NS1 proteins exhibited temperature sensitivity in virus protein synthesis at the translational level, as reported previously, and could not repress the autophosphorylation of PKR developing during the virus growth, which is normally suppressed by a viral function(s). As a result, the level of eIF2α phosphorylation was elevated 2.5- to 3-fold. The defect in virus protein synthesis was well correlated with the level of phosphorylation of PKR and eIF2α.